The Effect of Giving Trichoderma asperellum on Rice Plant Height in Organic and Inorganic Cultivation - Putri, Lidya Eka; Anhar, Azwir; Violita, Violita; Vauzia, Vauzia (Jurnal Biologi Tropis, 2024)
The agricultural sector cannot be separated from the role of inorganic fertilizers to support plant growth, as is the case with rice cultivation. Farmers' dependence on using inorganic fertilizers has led to decreased soil fertility and damage to natural resources. One way to overcome this is to implement organic farming. Organic cultivation in this research uses the SRI (System of Rice Intensification) method, while inorganic cultivation follows conventional methods from local communities. The aim of the research was to determine the effect of giving Trichoderma asperellum on rice plant height in organic and inorganic cultivation. The research was carried out in September-December 2022 in Jorong Galo gandang, Nagari III Koto, Tanah Datar Regency, Biological Research Laboratory, and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This type of research is experimental. The research was structured using a Randomized Block Design, with 4 treatments, namely; O (Organic) OT (Organic + Trichoderma asperellum), A (Inorganic), AT (Inorganic + Trichoderma asperellum) and 5 repetitions. Observational data was analyzed by analysis of variance (ANOVA) using the SPSS application. If there are differences, continue with the DNMRT test (Duncan's New Multiple Range Test). The results showed that giving Trichoderma asperellum had no significant effect on rice plant height in organic and inorganic cultivation. Because the high rainfall at the research location caused the nutrients from each experimental plot to be washed away by the water.